2007
DOI: 10.1016/j.brainres.2006.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal nitric oxide synthase is upregulated in a subset of primary sensory afferents after nerve injury which are necessary for analgesia from α2-adrenoceptor stimulation

Abstract: Abstractα2-Adrenoceptor (AR) agonists increase in analgesic potency and efficacy after peripheral nerve injury, and their effects are blocked by neuronal nitric oxide synthase (nNOS) inhibitors and M4 muscarinic receptor antagonists only after injury. We tested whether nNOS and M4 muscarinic receptors are co-expressed in the spinal cord, and whether destruction of a subset of sensory afferents which are essential to α2-AR analgesia would also destroy nNOS and M4 receptor expression.Male Sprague Dawley rats und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…This antibody specifically recognizes human, mouse and rat nNOS (Biomol data sheet). Antibody staining in mouse spinal cord reveals identical patterns to those previously documented (Maihofner et al 2000; Ma and Eisenach 2007). …”
Section: Methodssupporting
confidence: 81%
“…This antibody specifically recognizes human, mouse and rat nNOS (Biomol data sheet). Antibody staining in mouse spinal cord reveals identical patterns to those previously documented (Maihofner et al 2000; Ma and Eisenach 2007). …”
Section: Methodssupporting
confidence: 81%
“…24 It has been reported that the a 2 -agonists increase in analgesic potency and efficacy after nerve injury in animals 25 and patients with cancer pain. 26 In addition Ma and Eisenach 27 have reported that a 2 Agonists reduce injury-induced sensitization through the up-regulation of nitric oxide synthase.…”
Section: B Antinociceptive Role Of 2 -Adrenoceptorsmentioning
confidence: 98%
“…In addition, immunohistochemical, electrophysiological, and pharmacological studies have suggested that NO acts as a neu-rotransmitter or neuromodulator in the processing of nociceptive stimuli. However, the influences of NO upon nociceptive transmission at different levels of the spinal cord are opposing and complex, and the exact sites and mechanisms of these actions are controversial (Meller and Gebhart, 1993;Cížkova et al, 2002;Ruscheweyh et al, 2006;Boettger et al, 2007;Ma and Eisenach, 2007;Kawano et al, 2009). In fact, both hyperalgesic and analgesic effects of NO were demonstrated at different levels of the neuraxis (Hoheisel et al, 2005).…”
mentioning
confidence: 99%